Strategies for reducing financial security threats during wartime: Ukraine's experience - Shtantsel, Serhii; Amalian, Arutiun; Shevchenko, Bordan; Bulchak, Serhii; Kravets, Ruslan (Edelweiss Applied Science and Technology, 2024)
Minimising the impact of threats to financial security in wartime conditions is highly relevant to Ukraine, as the ongoing conflict significantly affects the country's economic stability and financial markets. Studying effective strategies and measures to reduce risks and protect the financial system is critical for ensuring sustainable economic development and maintaining citizens' trust in financial institutions. This research will contribute to a better understanding the mechanisms for countering financial threats and ensuring financial stability in crisis conditions. The study aims to develop ways to minimise the impact of threats to Ukraine's financial security in wartime conditions. The object of the study is Ukraine's financial system and its vulnerabilities in the context of military actions. The article examines strategies for reducing financial security risks in wartime conditions using a comprehensive approach that analyses economic, financial, and socio-political factors. The foundation of the research is a theoretical analysis of economic security and the application of systems analysis methods to identify critical threats. The research identified the main threats to Ukraine's financial security during wartime, including a significant decrease in foreign exchange reserves, rising inflation, increasing unemployment, and an outflow of investments. Several practical measures are proposed to minimise these threats. First, an effective system for monitoring financial risks to identify and respond to potential threats promptly must be created. Second, the banking sector should be strengthened by ensuring stability and increasing public confidence in financial institutions. Third, developing and implementing measures to stimulate domestic investment and support entrepreneurship. Additionally, the authors emphasise the need to enhance international financial support and cooperation with international financial organisations to attract additional resources. The practical significance of the obtained results lies in their potential use by the government and financial institutions to develop strategies and measures to ensure the country's financial stability in crisis conditions.